Hubungan Antara Persepsi Terhadapbeban Kerja DenganStres Kerja Pada Karyawanpt. Sri Rejeki Isman Tbk sukoharjo - Wijiningsih, Wijiningsih, Drs. Mohammad Amir,M.Si (2016)
High workloads can cause work stress on employees. Even in a work environment, most employees have experienced stress of work ranging from the lightest level though. This research aims to know the relationship between the perception against the workload with work stress on employees, to find out the effective contribution of the perception against the workload against work stress on employees, to know the level of perception against the workload on employees and to know the level of work stress on employees. The hypothesis of this research is there a positive relationship between the perception against the workload with work stress on employees. This research was conducted at 80 employees of PT Sri Rejeki Isman, Tbk. sampling using simple random sampling. Measuring instrument used is the scale of perception against the workload and work stress scale. Methods of data analysis used is parametric from Pearson with the help of computer program SPSS for Windows Version MS 15.00. Based on the results of data analysis, correlation coefficient value was obtained (r) of 0.914 with p = 0.000 (p < 0.001) means that there is a very significant positive relationships between the perception against the workload with work stress on employees of PT Sri Rejeki Isman, Tbk. effective Contributions from both variables are represented by coefficient a determinant (r ²) = 0.84 indicating that perception against work stress affects the workload of employees amounted to 84% and 16% of the remaining affected other variables. The variable perception against the workload has the empirical mean (RE) of 77.0875 and average hipotetik (RH) of 127.5 meaning ' perceptions towards the workload of employees classified as high. Work stress variables have the empirical mean (RE) of 141.2125 and average hipotetik (RH) amounted to 67.5 mean work stress were classified as employees. Keywords: work stress, workload, employees